Experiencia de los exportadores huilenses de tilapia en el uso del transporte aéreo de carga internacional. Laura Isabel Manios Hernández 20701919860 Universidad Antonio Nariño Programa Comercio (2023)
The present work refers to an investigation about the experiences of the commercialization and export of tilapia in the department of Huila, analyzing various aspects of the market to which the product is expected to finally reach, as is the case of the use of air transport of international cargo, in order to find the key elements to improve the effectiveness and efficiency of shipping activities. Likewise, a characterization of the current tilapia export companies that the department of Huila has was made, then it was known, what are the obstacles and / or barriers, challenges that the seven companies interviewed have, in this order of ideas The benefits and benefits offered by these organizations were found and finally their proposals were found, including suggesting to the Colombian State the possibility of receiving economic aid to maintain balance and increase productivity, likewise, to create a customs office in the Benito Salas airport of this city and that it is available at any time to facilitate the export of tilapia